The Financial System’s Resilience is Everything, But at what Cost? - Friesz, Melinda (Public Finance Quarterly, 2020)
The purpose of this study is to introduce the role of CCP in the market, the importance of the risk management framework, including the tools used in the case of insufficient guarantee funds. The study is descriptive, and besides detailing the EU-level regulatory framework, it also illustrates its possible setbacks from the perspective of the market participants and professionals. It points out that the common goal and interest of all actors are to ensure the viability of the CCP, but the poorly designed capital management and strategy can hinder this. Although the regulatory framework has been applied across Europe and its fine-tuning can be said to be constant, its effectiveness and resilience to shocks will be supported or refuted by an adverse event in the market.